PENGARUH JENIS PESAN PEMASARAN PRODUK FASHION MELALUI MOBILE MARKETING TERHADAP KEPERCAYAAN, RESPON DAN KEINGINAN PEMBELIAN KONSUMEN DI BANDUNG - Riandhita Eri Werdani; Robetmi Jumpakita Pinem; Nurul Imani Kurniawati (Faculty of Economics and Business Diponegoro University, 2018)
Mobile technology has emerged as a new potential tool for marketing activities. The emphasis of mobile phone marketing in this study is fashion mobile phone marketing via SMS or Blackberry Message. Message mobile phone marketing type is one of the importance to increase trust, response and purchase intention consumer. Consumer’s trust is importance factor which had significant influence on consumers’ purchase intention the fashion product. The aim of the study are to analyze the significant difference between message fashion mobile phone marketing type (community, website address, brand fashion product) with trust, response and purchase intention consumer in Bandung by using Anova and to understand the effect of message fashion mobile phone marketing type (community, website address, brand fashion product) on trust, response and purchase intention consumer in Bandung by using Conjoint analysis. The result of the study are there is significant difference between message fashion mobile phone marketing type (community, website address, brand fashion product) toward trust, response and purchase intention consumer in Bandung and the consumers prefer message fashion mobile phone marketing that send to community, include website address, and famous fashion brand.